Stage women, 1900-50 Female theatre workers and professional practice - Gale , Maggie B. (Manchester University Press, 2019)
Stage women, 1900-50 explores the many ways in which women conceptualised, constructed and participated in networks of professional practice in the theatre and performance industries between 1900 and 1950. A timely volume full of original research, the book explores women's complex negotiations of their agency over both their labour and public representation, and their use of personal and professional networks to sustain their careers. Including a series of case studies that explore a range of well-known and lesser-known women working in theatre, film and popular performance of the period. The volume is divided into two connected parts. 'Female theatre workers in the social and theatrical realm' looks at the relationship between women's work - on- and offstage - and autobiography, activism, technique, touring, education and the law. Part II, 'Women and popular performance', focuses on the careers of individual artists, once household names, including Lily Brayton, Ellen Terry, radio star Mabel Constanduros, and Oscar-winning film star Margaret Rutherford. Overall, the book provides new and vibrant cultural histories of women's work in the theatre and performance industries of the period.